Ecosystem resilience to the Millennium drought in southeast Australia (2001–2009). Issue 9 (14th September 2016) - Sawada, Yohei; Koike, Toshio
Abstract: The prolonged Millennium drought in southeast Australia (2001–2009) provides a unique opportunity to analyze the responses of a semiarid ecosystem to severe droughts. In this paper, we analyzed vegetation dynamics in the Millennium drought using visible/infrared observations, passive microwave observations, and a simple ecohydrological model. The satellite observations indicated that the ecosystem maintained its greenness in the Millennium drought, although the total aboveground biomass was significantly decreased by water scarcity. The results of our numerical experiments suggested that the resilience of vegetation greenness to the drought could be explained by a carbon allocation strategy that was sensitive to light and water availability and by temporal changes in vegetation traits. Our numerical experiments successfully simulated the decrease of total aboveground biomass with unchanged vegetation greenness during the Millennium drought. Key Points: In the Millennium drought in Australia the ecosystem decreased biomass but maintained greenness Carbon allocation strategies have an important role in responses to severe droughts Dynamic changes in ecosystem traits have an important role to responses to severe droughts